Potential of pepper plant accessions for ornamental purposes using diallel analysis - PESSOA,ANGELA M.S. (2019)
Abstract: The genus Capsicum is cultivated in various parts of the world, with C. annuum showing high diversity and potential for ornamental purposes and genetic improvement. The aim of this work was to evaluate the combining ability and heterosis of seedling and plant traits in accessions of ornamental pepper and their hybrids. Seven accessions of C. annuum were handcrossed and twelve quantitative plant traits were evaluated. The data were subjected to analysis of variance, the Scott-Knott test and diallel analysis using Griffing’s method I (fixed model). Heterosis and its components were also determined. Non-additive effects were found for seedling height, cotyledonous leaf length and width; stem diameter and chlorophyll b content. All other traits showed predominance of additive effects. Heterosis effects were found for some hybrids and UFPB134 x UFPB137, UFPB134 x UFPB390, UFPB134 x UFPB004 and UFPB099 x UFPB004 showed seedlings that are more vigorous.